2022
DOI: 10.32604/phyton.2022.019219
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Unique Germacrene A Oxidase from Xanthium strumarium

Abstract: 8,12-sesquiterpene lactones (STLs) are an important class of natural products with unique pharmaceutical activities. For years the pathway leading to 8,12-STLs remains an enigma. Xanthium strumarium accumulates abundant 8,12-STLs, and xanthatin is a characteristic 8,12-STL in it. Xanthatin has been previously postulated to be derived from germacrene A, but the steps from germacrene A to xanthatin are unknown. As part of an effort to understand the xanthatin biosynthetic pathway. This study reports the characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…GAO isolated from L. sativa was expressed in an engineered yeast to synthesize GAA de novo, and the classical GAO activity involved three-step oxidation of germacrene A (GA) to yield GAA and 12,6-guaianolides [ 25 , 34 ], similar to N. benthamiana [ 35 ]. Meanwhile, an Xs GAO from X. strumarium catalyzed only one-step conversion of germacrene A to germacrene alcohol [ 36 ], but this study clearly shows that Xs GAO1 and Xs GAO2 catalyzed a second step of oxidation of the non-natural substrate germacrene A to germacrene A acid, which was not observed in yeast with a different GAO. Apparently, Xs GAO2 is a unique enzyme, a functional adaption of SLTs’ biosynthetic pathway diversification.…”
Section: Discussionmentioning
confidence: 85%
“…GAO isolated from L. sativa was expressed in an engineered yeast to synthesize GAA de novo, and the classical GAO activity involved three-step oxidation of germacrene A (GA) to yield GAA and 12,6-guaianolides [ 25 , 34 ], similar to N. benthamiana [ 35 ]. Meanwhile, an Xs GAO from X. strumarium catalyzed only one-step conversion of germacrene A to germacrene alcohol [ 36 ], but this study clearly shows that Xs GAO1 and Xs GAO2 catalyzed a second step of oxidation of the non-natural substrate germacrene A to germacrene A acid, which was not observed in yeast with a different GAO. Apparently, Xs GAO2 is a unique enzyme, a functional adaption of SLTs’ biosynthetic pathway diversification.…”
Section: Discussionmentioning
confidence: 85%
“…An important class of natural products with a unique pharmaceutical activity is 8,12-sesquiterpene lactones (STLs). Zheng et al (2022) reported about a unique germacrene А oxidase (XsGAO) from X. strumarium. Unlike the classic enzyme GAO, which catalyzes the three-stage oxidation of germacrene А with formation of germacrene acid A (GAA), XsGAO catalyzes only one-stage transformation of germacrene into germacrene alcohol (Zheng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al (2022) reported about a unique germacrene А oxidase (XsGAO) from X. strumarium. Unlike the classic enzyme GAO, which catalyzes the three-stage oxidation of germacrene А with formation of germacrene acid A (GAA), XsGAO catalyzes only one-stage transformation of germacrene into germacrene alcohol (Zheng et al, 2022). Sahu et al (2010) evaluated the pharmaceutical properties of the leaves of X. strumarium, finding that alcohol extract exerted a significant anti-inflammatory, anesthetic, and antimicrobial actions.…”
Section: Discussionmentioning
confidence: 99%